Pengaruh Ekstrak Daun Turi Merah Terhadap Kadar Tgf-Î² Pada Mencit Model Infeksi Nifas - VeronikaWidiatrilupi, Raden Maria (Journal of Islamic Medicine, 2017)
Puerperalis infection is a common problem for post-partum mothers in developing countries. Bacteria commonly found in postpartum infections one of them is the gram-positive bacterium Streptococcus agalactiae. 5-30%. Postpartum infection caused by this bacteria is endometritis. Streptococcus agalactiae is a gram-positive bacterium in the form of coccus which produces toxin in the form of cytotoxic exotoxins and bacterial cell wall components. The body has a mechanism to offset the Th1-mediated excess proinflammatory immune response, which is the Th2 response that induces the production of Transforming Growth Factor (TGF-Î²). The purpose of this paper to prove red turi leaf extract can affect the levels of TGF-Î² in the mice of infertile infection inoculated by Sterptococcus agalactiae bacteria.